Urinary Tract Infection in Children Presenting with Nephrotic Syndrome - Sumera Abdul Karim, Nadia Ejaz, Muhammad Wasim Salim, Maha Anwar, Mahjabeen Akram, Sumbal Abbas, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Nephrotic syndrome, or nephrosis, is defined by the1presence of nephrotic-range1 proteinuria, edema, hypoalbuminemia & hyperlipidemia. Nephrotic syndrome remains the common manifestation of glomerular disease in childhood. UTI is a common infection accompanying nephrotic syndrome. But there is no local evidence available. Aim: To assess the frequency of urinary tract infection in children presenting with nephrotic syndrome in a tertiary1care hospital. Study design: Cross sectional study. Methodology: Total 280 children fulfilled the inclusion criteria were included through non-probability convenience sampling. Urine sample was obtained in sterile container & was sent to the pathology1laboratory of the hospital. Then reports were assessed & if pathogen was present, then UTI was labeled. Data was evaluated by using SPSS v.24. Quantitative data was presented as mean±SD. Qualitative data was presented as frequency and percentage. Chi-square test was applied with P-value ≤0.05 taken as significant. Results: The mean age was 7.07±3.09years. There were 152(54.3%) males and 128(45.7%) females. The mean weight of patients was 24.30±7.75kg. The mean duration of nephrotic syndrome was 9.66±5.37months. There were 147(52.5%) patients who had UTI while 133(47.5%) patients did not have UTI. Practical Implication: As there is a high incidence of UTI among nephritic children and there is lack of local data that specifically addresses this health issue thus current study was planned. Results regarding precise estimate of UTI frequency in nephrotic syndrome patients helped to formulate recommendations for early screening to initiate early management of UTI. This information also helped in reducing morbidity and mortality in children with nephrotic syndrome. Conclusion: It was concluded that frequency of UTI was high in children with nephrotic syndrome hence screening of UTI is necessary on regular intervals in children with1nephrotic syndrome. Keywords: Urinary Tract Infection, Nephrotic Syndrome, Children, Proteinuria and Albuminuria.